Generalist Palliative Care in the California Safety Net: A Structured Assessment to Design Interventions for a Range of Care Settings. (January 2021) - Anderson, Wendy G.; Parrish, Monique; Kerr, Kathleen; Kinderman, Anne; Rabow, Michael; Schoen, Melissa; Meyers, Kate
Background: To provide high quality care to all patients who have serious illness, health-care systems must develop effective generalist palliative care strategies. Objective: To identify palliative care quality gaps within a range of settings in the California safety net and to develop theory-based interventions to address them. Design: Structured assessment using the National Consensus Project for Quality Palliative Care Clinical Practice Guidelines and a Predisposing, Reinforcing, and Enabling Constructs in Educational/Environmental Diagnosis and Evaluation intervention planning model-based worksheet, which integrates behavior theories to identify factors that predispose, enable, and reinforce clinicians to perform recommended behaviors. Setting and Participants: Adviser pairs—one from palliative care and one from a partner service line—from 10 California public health-care systems conducted assessments at their sites. A steering committee provided educational webinars, best practices, and assessment tools. Measurements: Adviser pairs interviewed at least 6 partner service line stakeholders to identify palliative care quality gaps, behaviors clinicians should perform to close gaps, and factors that predispose, enable, and reinforce those behaviors. Results: Partner service lines were primary care (n = 4), surgery (n = 3), emergency department (n = 2), and radiation oncology (n = 1). Selected gaps were advance care planning and goals of care communication (n = 6), identifying patients with serious illness (n = 3), and pain management (n = 1). All sites designed multiple interventions to address gaps, based on factors that predispose, enable, and reinforce a target audience to perform a target behavior. Advisers reported that the program strengthened relationships between palliative care and the partner service line Conclusion: This structured assessment helped busy clinicians develop theory-based generalist palliative care interventions.